Monocular temporal hemianopia. - Hershenfeld, S. A. (1993)
Monocular temporal hemianopia was identified in 24 patients. The field of the fellow eye was normal. Computed tomography or magnetic resonance imaging showed juxta-sellar lesions in 19 patients. Fifteen had pituitary adenomas, two had tuberculum sella meningiomas, one a craniopharyngioma, and one an astrocytoma. One patient had optic neuritis. A relative afferent pupillary defect (RAPD) was detected in most patients. Field loss was functional in two. Two had congenital optic disc dysversion with hemianopia which did not respect the vertical meridian. Monocular temporal hemianopia is attributed to involvement of the ipsilateral optic nerve close enough to the chiasm to selectively impair conduction in crossing nasal retinal fibres from the ipsilateral eye, but too anterior to affect crossing nasal retinal fibres from the contralateral eye. The combination of an RAPD, with or without optic disc pallor, on the side of monocular temporal field loss implicates compression of the optic nerve at its junction with the chiasm.